Developing STEM-Based PowToon Animation Videos to Enhance Critical Thinking Skills in Elementary School Students - Indri Widayanti; Juhji Juhji (Journal of Integrated Elementary Education, 2023)
This article examines the utilization of the PowToon animated film, integrated with the STEM (Science, Technology, Engineering, and Mathematics) approach, in enhancing the critical thinking skills of primary school students. Employing the ADDIE model methodology, this research involved 20 students as its subjects. Data collection techniques included observation, questionnaires, and evaluation of critical thinking skills. During the analysis phase, expert validation served as the foundational consideration, and the results of the students' critical thinking skills test were subsequently analyzed comparatively. The findings revealed that the PowToon animation with the STEM approach received positive feedback from experts, with scores of 92.50% from subject matter specialists, 89.50% from media experts, and 91.00% from linguistic authorities. When the topics of temperature and heat were presented through this animation, a significant improvement in the students' critical thinking abilities was observed. In conclusion, the STEM-based PowToon animation demonstrates its potential as an innovative and effective educational tool.